Design of GeoAi-Based Control Tower Dashboard Application Infrastructure at PT. XYZ - Siregar, Maulana Bobby Rakhman; Aji, Rizal Fathoni (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The increasing demand for technology and data necessitates the enhancement of infrastructure for the Control Tower Dashboard Geographic Information System (CTD GIS) application at PT XYZ. The current system operates within a Virtual Private Server (VPS) Cloud environment but faces challenges such as data loading delays and increasing demands for broader functionalities. To address these issues, a comprehensive future infrastructure recommendation is outlined, including upgrading ArcGIS Server, integrating with Portal for ArcGIS, implementing ArcGIS Datastore, utilizing NAS Storage, and incorporating Script & VGA Server. Through the proposed infrastructure changes, the CTD GIS application is poised to navigate the dynamics of data growth, providing geospatial insights to support better decision-making processes at PT XYZ.